Evaluasi Ketahanan Varietas Cabai Rawit Terhadap Penyakit Antraknosa (Colletotrichum Gloesporioides) Asal Isolat Dari Cabe Hiyung - Amalia Fauziah; Mariana .; Ismed Setya Budi (www.ulm.ac.id, 2024)
The category of resistance level of several cayenne pepper varieties planted in swamps to anthracnose disease (Colletotrichum gloesporioides) originating from isolates from hiyung chilies is important to know as basic information for determining control strategies. This research aims to determine the level of resistance of several varieties of cayenne pepper planted in swamp land to anthracnose isolates from Hiyung chilies. This research used RAL (Completely Randomized Design) with 10 treatments and 3 replications and 2 plants were used in each replication so that the total number of plants was 60 plants. The varieties used are the Bara, Hiyung, Dewata 43 F1, Tiung Tanjung, Tiung Ulin, Genie, Sekar, Alip, Sret and CR-9 varieties. Inoculation of the fungus Colletotrichum gloesporioides was carried out at the time of fruiting, with variables observed, namely the incubation period and disease incidence. The results of the research show the resistance of chili plants to anthracnose disease in the susceptible category, namely the Hiyung variety with a disease incidence percentage of 42.08%. The moderate category is the Bara, Dewata 43 F1, Tiung Tanjung, Genie, Sekar, and CR-9 varieties with disease incidence percentages of 30.11%, 28.94%, 35.93%, 20.87%, 21, respectively. 52% and 28.20%. The resistant category is the Tiung Ulin, Alip and Sret varieties with disease incidence percentages of 18.37%, 19.36% and 17.11% respectively. The incubation period for several cayenne pepper varieties that have been tested varies with an average of between 3.5-5.3 days.